Factors Affecting Lymph Node Yield in Surgically Resected Colorectal Cancer Specimens - Nagarajan, Deepa; Jain, Rupa Ashish; Shah, Anita Bharat; Munde, Rajesh; Shah, Mita Y (Annals of Pathology and Laboratory Medicine, 2021)
Background: Currently, the CAP protocol mandates evaluation of â‰¥12 Lymph nodes as a quality indicator for the adequacy of pathologic examination of colorectal cancer resection specimens. Aim: To identify factors that may influence the lymph node yield in colorectal cancer specimens and to compare with the relevant publications. Methods: The retrospective study of seventy patients with loco-regional colorectal adenocarcinomas treated by standard surgical resection from April 2015- April 2017 was included. All cases with inadequate lymph nodes had been re-grossed by another pathologist. Variables like age, gender, primary site, type of surgery, specimen length, tumour size, grade and stage, neoadjuvant therapy and tumour site perforation were evaluated for their impact on the average total number of nodes examined. Results: Out of seventy, eleven [15.71%] patients had inadequate mean nodal yield [MNY]. Of these eleven patients, MNY was greater in males [6.6] than in females [6.4]. MNY was lesser in patients with age >50years [5.71] than patients â‰¤ 50 years [8]. The yield increased exponentially with increasing tumour stage and tumour size. Yield was higher in tumours with perforation. Specimens longer than 20cm had a higher yield [7.29] than in shorter specimens [5.25]. The yield was lesser when tumour is located more distally [APR:4.5 and AR &sigmoid colectomy:7.7]. Seven patients had taken neoadjuvant therapy [63.6%] of whom, six had moderately differentiated adenocarcinoma & one had no tumour. Conclusion: Factors like neoadjuvant therapy, age & gender of the patient, type of surgery, length of the specimen, tumour size, grade, stage, site & perforation, affect the MNY in colorectal cancers.